Personalizm tomistyczny wobec nowoczesnej i ponowoczesnej antropologii - Andrzejuk, Artur (Studia Theologica Varsaviensia, 2018)
Thomistic personalism against modern and postmodern anthropology Summary The article is divided into four parts which discuss the following subjects: 1) Anthropology of the late 19th and mid-19th century – consisting in the evolutionary understanding of not only the genesis of man but also his personality, psyche, culture and morality. This approach contrasted with the Thomistic theory of man as a person, which was developed also at this time. Man understood as a person can be characterized by the intellectual perception of the surrounding reality, the freedom to act, and the love for others which goes beyond purely physical relations. A human being understood in such a way stands in opposition to every form of reductionism: biological, sociological, cultural, economic, and legal. Man as a person grows above the physical, also above his body which – despite being an integral part of human existence – does not fall within the definition of a person. According to this view, man cannot be reduced to his body, which is obvious, but also carnality does not constitute a central theme of anthropology, that being a person. As a consequence, the problem of the origin of the body becomes secondary and from this perspective, even the acceptance of the evolutionary origin of the bodily organs does not constitute a ground for negating the creative role of God in the formation of man. 2) Anthropology of postmodernism is characterized by the “fluidity” of the definition of man. This is caused by the “contingency” of man, which points to individuality, diversity and lack of one metaphysics that could cover all objects. A postmodern man believes in historicism (looking at phenomena from the point of view of their historical evolution) and nominalism (there are only individuals and their conventional names), so he can abandon any metanarrative attempts to describe the essence of things. He creates his own language of metaphors which he can use absolutely freely. According to the theory of man as a person, postmodernism appears as a reaction to the biological and socio-cultural reductionism that the science of the 19th and 20th century – with its scientism and technocracy – offered to man. It seems that in this context one can pay attention to the typical characteristics of a person (constitutiva personae), such as individuality, intellectual character and freedom of the human being, which all give rise to its subjectivity and far-reaching autonomy. 3) Anthropology of transhumanism advocates the widespread use of medical science (including manipulation of the DNA code) and advanced technology in human development, leading to the transformation of man into the posthuman and beginning a new epoch of history called posthumanism. Posthumans will be beings with far greater capabilities than human beings today. In a discussion with transhumanism, the article referred to the fundamental paradigms of philosophical thinking – Platonism and Aristotelianism. It was considered that transhumanism is a form of Platonism with its dream of making man angelic or divine. It results from the concept of man as only the set of attributes and relations “mechanically” added to each other. According to Aristotelianism, the form of human being is immutable in its essence, and it is only the properties and relationships of a human being that change. The Thomistic theory of a person belongs to a group of philosophies originating from the Aristotelian school and – allowing for a great variability of features and relationships – it does not consider them to be able to change their subject – a human being into something else. 4) Social philosophers and philosophical sociologists record a number of negative anthropological phenomena related to the already existing postmodern and transhumanist “project”. These include primarily nihilism, scientism, materialism, and identity loss, all of which results in the infantilization of the human culture, and – in the economic field – in the economy of excess and lack, i.e. the continuous deepening of financial differences (fortifications of the rich and ghettos of the poor), while in the area of health it leads to the deterioration of the mental condition of man. It is suggested that the subjective and personal approach to man be opposed to extreme scientism, nihilism and the objective and utilitarian use of man for the benefit and pleasure. Finding oneself as a person can be a way for people to get to know themselves and overcome a deepening identity crisis. Emphasizing the dignity of the person and concern for the common good may be an attempt to leave the civilization of excess and lack. Establishing personal relationships and caring for others can inhibit the breakdown of interpersonal relationships, loneliness and the loss of a sense of security, and it may help improve the deteriorating spiritual condition of the postmodern human.